Rizzoli & Isles Season 2 Disc 2 - Gerritsen, Tess.; Tamaro, Janet; Haber, Bill.; Fields, Joel.; Bracco, Lorraine, 1955-; Harmon, Angie, 1972-; Young, Lee Thompson, 1984-2013.; McGill, Bruce, 1950-; Bridges, Jordan, 1973-; Alexander, Sasha, 1973-; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2012)
Homicide detective Jane Rizzoli and forensic pathologist Maura Isles are close friends, complete opposites and on the case in all 15 gritty episodes based on the best-selling novels by Tess Gerritsen. Season Two sees brash Jane healing emotional and physical scars as old loves re-appear and her mother Angela deals with divorce. Meanwhile, Jane's ex-con brother Tommy has eyes for cerebral Maura, whose own family life is complicated by her adoptive mother Constance.
6. Rebel without a pause -- 7. Bloodlines -- 8. My own worst enemy -- 9. Gone daddy gone -- 10. Remember me.
Title from container and disc label.
Originally broadcast on television in 2011.
Release date: May. 22, 2012.
Lorraine Bracco, Angie Harmon, Lee Thompson Young, Bruce McGill, Jordan Bridges, Sasha Alexander.
Rating: NR.
DVD, widescreen; Dolby surround 5.1.
Keywords: Isles, Maura -- (Fictitious character); Rizzoli, Jane, -- Detective (Fictitious character); Policewomen -- Massachusetts -- Boston -- Drama; Medical examiners (Law) -- Massachusetts -- Boston -- Drama; Criminal investigation -- Massachusetts -- Boston -- Drama; Drama; Medical television programs; Television cop shows; Television series; Video recordings for the hearing impaired